2014
DOI: 10.1080/10934529.2014.865401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural acids on surface properties of asbestos minerals and kaolinite

Abstract: Serpentine, and other asbestos minerals, are considered potential hazards to human respiratory health. It has been postulated that the surface characteristics of these substances, such as surface charge and adsorbed metals, notably Fe and other transition metals, may be the major agents responsible for their toxicity. There is a general consensus that the amphibole group of minerals possesses a greater health risk than serpentines dominated by chrysotile. There have been suggestions that natural processes can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As a consequence, many chrysotile waste treatments by acid attack have been proposed. As an example, the use of strong acids such as hydrochloric acid [36,37], sulfuric acid [38] or nitric acid [39] were used to treat waste. Other studies propose the use of weaker acids to overcome the problems of acid management, with the use of organic acids such as oxalic [40,41], acetic or formic acid [9].…”
Section: Asbestos Treatment Technologiesmentioning
confidence: 99%
“…As a consequence, many chrysotile waste treatments by acid attack have been proposed. As an example, the use of strong acids such as hydrochloric acid [36,37], sulfuric acid [38] or nitric acid [39] were used to treat waste. Other studies propose the use of weaker acids to overcome the problems of acid management, with the use of organic acids such as oxalic [40,41], acetic or formic acid [9].…”
Section: Asbestos Treatment Technologiesmentioning
confidence: 99%
“…According to its structure, Mg-octahedral sheet is bonded to Si-tetrahedral via O-atoms [8]. Besides its strict structure, strong acids such as HCl, H 2 SO 4 , and HF [9][10][11] have already been used to destroy the external sheet of brucite. However, these acids are harmful to human health and should be avoided [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the leaching of asbestos due to soil deposits in streams and the weathering of asbestos-bearing rocks, reduces the concentrations of PTEs in the elongate mineral particles and increases them in the soil (Holmes et al, 1971;Kumar and Maiti, 2015). In this regard, it has been demonstrated that some acids alter the mineral surface of asbestos and remove considerable amounts of PTEs (Lavkulich et al, 2014). Therefore, resembling the original contents, soils developed from ophiolitic rocks are 6 characterized by high concentrations of PTEs, in particular Mn, Cr, Ni and Co (Lyon et al, 1968;1970;Atzori et al, 1999;Oze et al, 2004;Smith et al, 2007;Rajapaksha et al, 2012;Kelepertzis et al, 2013;Vithanage et al, 2014;Baumeister et al, 2015;Bloise et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%